2018
DOI: 10.3390/ijerph15122804
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological Benefits of Walking through Forest Areas

Abstract: This study aimed to clarify the psychological benefits of brief walks through forest areas. In addition, we aimed to examine the associations between psychological responses and trait anxiety levels. Five-hundred-and-eighty-five participants (mean age, 21.7 ± 1.6 years) were instructed to walk predetermined courses through forest (test) and city (control) areas for 15 min. The Profile of Mood State (POMS) questionnaire and State-Trait Anxiety Inventory were used to assess participants’ psychological responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 41 publications
8
98
0
1
Order By: Relevance
“…Scores for the comfortable, relaxed, and natural parameters, as well as the vigor subscale of the POMS, were significantly higher after viewing a forest landscape than after viewing a city area, whereas the scores for the subscales for negative feelings, including tension-anxiety, depression-dejection, anger-hostility, fatigue, and confusion, were significantly lower, as was the total mood disturbance score and the STAI anxiety dimension score. These results, which demonstrate the psychological benefits of viewing a forest, are to some extent consistent with previous findings of the effects on men of viewing forest scenery or walking in forests [12,14,[50][51][52].…”
Section: Discussionsupporting
confidence: 91%
“…Scores for the comfortable, relaxed, and natural parameters, as well as the vigor subscale of the POMS, were significantly higher after viewing a forest landscape than after viewing a city area, whereas the scores for the subscales for negative feelings, including tension-anxiety, depression-dejection, anger-hostility, fatigue, and confusion, were significantly lower, as was the total mood disturbance score and the STAI anxiety dimension score. These results, which demonstrate the psychological benefits of viewing a forest, are to some extent consistent with previous findings of the effects on men of viewing forest scenery or walking in forests [12,14,[50][51][52].…”
Section: Discussionsupporting
confidence: 91%
“…As Bowler et al (5) reported, 13 studies on the effects of walking in natural environments were published between 1991 and 2008, most of which reported that nature therapy decreased negative emotions, such as anger, fatigue, and sadness, and enhanced positive emotions, such as energy. The psychological benefits of forest-walking have been supported by many subsequent studies (6,7). However, the benefits of forest-walking are not only psychological.…”
Section: Introductionmentioning
confidence: 95%
“…Since the 1990s, a growing number of studies have been focused on a comparison of natural and built-up urban environments [6][7][8] showing mostly beneficial effects of the natural environment for human health and well-being. There are several studies indicating the effectiveness of forest visits (in comparison to a build-up environment) on mental health, depression and anxiety among people [9][10][11][12]. There is also evidence that a short walk in a forest environment might also have a therapeutic impact on mental hospital patients with affective and psychotic disorders [13].…”
Section: Nature and Human Healthmentioning
confidence: 99%
“…The direct impact of the forest environment can be measured by staying in the forest. For this purpose, the simulation of various activities is used: using the forest environment during the camp [49], walking [9] or sitting and relaxing [17]. Control is often used, such as being in an urban environment, where a negative effect on the psychological and physiological well-being of the subjects has been observed [50].…”
Section: Virtual Nature Environmentsmentioning
confidence: 99%